1992
DOI: 10.1620/tjem.166.471
|View full text |Cite
|
Sign up to set email alerts
|

Brunnstrom Stages and Wallerian Degenerations: A Study Using MRI.

Abstract: Kanagawa 243WATANABE, H. and TASHIRO, K. Brunnstrom Stages and Wallerian Degenerations : A Study Using MRI. Tohoku J. Exp. Med., 1992, 166 (4), [471][472][473] We studied the relationship between the Brunnstrom stages obtained after rehabilitations and Wallerian degenerations detected by magnetic resonance imaging (MRI). Forty-nine hemiplegic patients were retrospectively studied. The patients were grouped into a low stage group (30 patients) demonstrating Brunnstrom stages I -IV and a high stage group (19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The pre‐stroke required level of care was confirmed through certification for public long‐term care insurance, with categories ranging from “Care level 1”– can perform almost all ADL, but partial care is required, to “Care level 5” – must be aided in all situations and had difficulty with communication. We evaluated the degree of lower limb motor paralysis by using the Brunnstrom recovery stage system (BRS) . In our current study, the patients were classified by this approach into three groups; Brunnstrom recovery stage I–IV, Brunnstrom recovery stage V–VI and “absence.” Lower limb motor paralysis and FIM status were evaluated by physical therapists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre‐stroke required level of care was confirmed through certification for public long‐term care insurance, with categories ranging from “Care level 1”– can perform almost all ADL, but partial care is required, to “Care level 5” – must be aided in all situations and had difficulty with communication. We evaluated the degree of lower limb motor paralysis by using the Brunnstrom recovery stage system (BRS) . In our current study, the patients were classified by this approach into three groups; Brunnstrom recovery stage I–IV, Brunnstrom recovery stage V–VI and “absence.” Lower limb motor paralysis and FIM status were evaluated by physical therapists.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the degree of lower limb motor paralysis by using the Brunnstrom recovery stage system (BRS). 18,19 In our current study, the patients were classified by this approach into three groups; Brunnstrom recovery stage I-IV, Brunnstrom recovery stage V-VI and "absence." Lower limb motor paralysis and FIM status were evaluated by physical therapists.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…4, 815 Furthermore, evidence of CST atrophy and other signal changes thought to be indicative of WD on conventional MRI 16 have been correlated with poor motor outcome in chronic stroke patients. 17, 18 It seems that these changes develop at later stages and might be too subtle to be quantified in the acute stroke phase and therefore might not be useful as a prognostic tool for clinicians, patients, and caregivers. 19 One prospective study found a decrease in the apparent diffusion coefficient (ADC) of the ipsilesional CST within 12 hours of stroke in patients with initial severe motor impairment 20 , but predictions of outcome were not very strong.…”
Section: Introductionmentioning
confidence: 99%
“…The patients in our study were specifically recruited for mildto-moderate chronic hemiparesis and, thus, were likely to have CST injury. [20][21][22][23] We hypothesized that in such patients the hemispheric extent of lesion to the CST would significantly correlate with the extent of cerebral peduncular atrophy and to a greater extent than would the volume of the infarction. Such a finding would suggest that a simple, predictable relationship exists between the amount of postinfarction structural injury at discrete and widely separated portions of the same fiber tract.…”
mentioning
confidence: 99%